Population Study Of The Amorphophallus titanum Becc In Sumatera - Faristy, Annisya Fhadilah Putri; vauzia, Vauzia (Universitas Andalas, 2024)
Amorphophallus has 176 species spread throughout the world, 25 of which are found in Indonesia. Of the 25 species found in Indonesia, 8 of them are endemic to Sumatra. One type of Amorphophallus found on the island of Sumatra is Amorphophallus titanum, whose survival in its natural habitat is threatened by deforestation and forest degradation. As an endemic plant, A. titanum is also more vulnerable to anthropogenic threats and environmental change, and therefore faces a greater risk of extinction than more widespread species. To prevent species extinction and as a form of biodiversity conservation, information is needed that presents the population status of A. titanum in its natural habitat. This article aims to provide information about the population of corpse flowers (Amorphophallus titanum Becc) in Sumatra. The research method used is a literature review. Data was obtained from journals and articles published from 2005 to 2023. Based on research conducted, it is known that A. titanum is often found in Bengkulu, Lampung, Jambi, North Sumatra and West Sumatra. The highest population of A. titanum is in Muara Hemat Village, South Kerinci Resort, Kerinci Seblat National Park, Jambi, with a total of 83 individuals. In Bengkulu, A. titanum is found in several locations; in KHDTK (Forest Areas with Special Purposes) as many as 64 individuals. At Ketapang Water, Jufi Hill and Datar Lebar Waterfall there were 56 individuals. In the Mount IV Kepahiang Nature Reserve there are 56 individuals. In Tebat Monok, Air Selimang and Palak Siring the number is 52 individuals. Meanwhile in North Sumatra, specifically in the Sibolangit Nature Reserve, Sibolangit Nature Reserve, Dolok Sipirok Nature Reserve, and Namo Suro Baru Village, 32 individuals were found. In Palupuah, Agam Regency, and South Solok, West Sumatra, there are 24 individuals, and also in the Liwa Botanical Gardens, Lampung, there are 4 individuals.